From Beverages to Biofuels: The Journeys of Ethanol-Producing Microorganisms - Macedo, Nicholas; Brigham, Christopher J. (International Journal of Biotechnology for Wellness Industries, 2014)
Microbial fermentation for bio-based products is quickly becoming an integral component of the world infrastructure, as the processes encompassing the synthesis of these natural products becomes more efficient and cost effective to compete with existing commodities. Bioethanol is currently one of the most desired fermentation products, as this constituent can be applied to multiple uses in not only contributing to the more traditional routes of beer brewing and winemaking, but also in the foundation for green fuel sources. By optimizing yields, the innovative processes could be applied towards engineering more rapid and productive biomanufacturing. In order to achieve these goals, we as researchers must understand the underlying principles and intricate networks that play a role within the microenvironment and also on the cellular level in key fermentative microbes such as Saccharomyces cerevisiae and Zymomonas mobilis. In-depth pathway analysis could lead to the development of more favorable metabolic outcomes. This review focuses on the key metabolic networks and cellular frameworks in these model organisms, and how biosynthesis of ethanol yields can be optimized throughout the fermentation process.